KARAKTERISASI EKSTRAK KULIT UBI JALAR UNGU (Ipomea batatas L Poir) BERDASARKAN BEBERAPA PARAMETER SPESIFIK EKSTRAK - Nurul Hidayah Base; Raymond Arief N Noena; Adnan Ahmad (Jurnal Kesehatan Yamasi Makassar, 2026)
Anthocyanin is a secondary metabolite of plants that can be used as a natural dye. Purple sweet potato (Ipomea batatas L Poir) is a food ingredient known to contain high anthocyanin compared to other types of sweet potatoes. Purple sweet potato skin which is usually not used can be used as an alternative to obtain anthocyanin as a natural dye. This study aims to determine the characteristics of purple sweet potato skin extract including extract soaking, water content, watersoluble extract content, ethanol-soluble extract content as standard parameters of extract quality. The study showed that the sweet potato skin extract produced was a thick extract, dark purple in color, slightly sweet in taste and distinctive odor, extract soaking value of 7.86% water content 15.28%, watersoluble extract content 32.82% and ethanol-soluble extract content 18.06%.